Pursuance of academic music studies by popular Zimbabwe musicians - Wonder Maguraushe; Phineas Magwati (Utafiti Foundation, 2023)
Some popular musicians in Zimbabwe have taken up professional development seriously and enrolled in academic music studies, yet no research has been done to explore this recent phenomenon. Whenever the subject of Zimbabwean music is discussed, the focus tends to centre on popular artists, their lifestyles, achievements and scandals. The emerging trend in which Zimbabwean artists are enrolling for academic programs has received little scholarly interrogation. This is the scenario despite the fact that education is the backbone for the development of the music industry, which is part of the United Nations` Sustainable Development Goals. The main aim of this article is to consider how music studies impact and broaden the scope of the artists and contribute to the betterment of the Zimbabwe music industry. In this qualitative study, we purposively sampled and interviewed 7 popular Zimbabwean musicians who embarked on academic music studies. Data were collected through key informant interviews to solicit their views on the value that music education adds to their professional careers in terms of transforming their performances, compositions and application of music theory to analyses musical issues, as well as observations and document analysis. The study was guided and informed by the theory of stereotype and Dweck`s theory of mind-set. The findings steer an interesting discussion in which the musicians indicate how their capabilities and conduct of business are polished by their interaction with academia. We argue that the acquisition of professional academic qualifications by popular musicians adds value to their acts and encourage untrained musicians to seriously consider trudging the academic route for the development of the Zimbabwe music industry to realise its full potential.